(untitled) (Innovative professional education, 2024)
The analyses the quality of vocational education in the context of lifelong learning and development. The key factors that determine the quality of education are explored, current challenges to its accessibility are considered, and potential strategies for improving the vocational education system to meet the needs of a constantly changing society are proposed.